2015
DOI: 10.3389/fmicb.2015.00809
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the bacterial community and its temporal succession during the fermentation of wine grapes

Abstract: Grapes harbor complex microbial communities. It is well known that yeasts, typically Saccharomyces cerevisiae, and bacteria, commonly the lactic acid fermenting Oenococcus oeni, work sequentially during primary and secondary wine fermentation. In addition to these main players, several microbes, often with undesirable effects on wine quality, have been found in grapes and during wine fermentation. However, still little is known about the dynamics of the microbial community during the fermentation process. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 42 publications
9
47
1
Order By: Relevance
“…Taxonomical assignments showed that most OTUs found in the Chilean vineyard samples corresponded to the fungal and bacterial species commonly found in grapes or grape must in various world wine regions (Bokulich et al ., ; Taylor et al ., ; Piao et al ., ; Pinto et al ., ; Portillo et al ., ). Relative abundance analysis of the fungal OTUs showed that Dothideomycetes was the most abundant taxonomical class, which made up 78%–96% of the total sequences of each sample (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Taxonomical assignments showed that most OTUs found in the Chilean vineyard samples corresponded to the fungal and bacterial species commonly found in grapes or grape must in various world wine regions (Bokulich et al ., ; Taylor et al ., ; Piao et al ., ; Pinto et al ., ; Portillo et al ., ). Relative abundance analysis of the fungal OTUs showed that Dothideomycetes was the most abundant taxonomical class, which made up 78%–96% of the total sequences of each sample (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The food safety of some spontaneously fermented foods can be questioned because of the presence of pathogens in the initial food matrix. HTS has successfully been used to determine the population dynamics of microbial consortia in a variety of fermented foods, including bacterial community temporal succession during the fermentation process of wine grapes (Piao et al, 2015), sourdoughs (Weckx et al, 2010;Ercolini et al, 2013), Mongolian fermented cow's milk , mozzarella cheese (Ercolini et al, 2012), and kimchi (Jung et al, 2011).…”
Section: Investigation Of the Microbial Dynamics Of Fermented Foodsmentioning
confidence: 99%
“…3) using a logistic regression model that has been widely used to analyze and predict microbial growth (Piao et al 2015). Total VFA also showed similar trend of decreasing during the first 6 days at period 3.…”
Section: Discussionmentioning
confidence: 86%